Baicalin Ameliorates Liver Injury Induced by Chronic plus Binge Ethanol Feeding by Modulating Oxidative Stress and Inflammation via CYP2E1 and NRF2 in Mice. (16th August 2017) - He, Ping; Wu, Yafeng; Shun, Jianchao; Liang, Yaodong; Cheng, Mingliang; Wang, Yuping
Abstract : Alcoholic liver injury leads to serious complication including death. The potential role of baicalin at the transcription level in mice model of alcohol injury is not known yet. In this study, we examined the effect of baicalin against chronic plus binge ethanol model in mice and understanding the mechanism of protection. Liver function, histology, steatosis, inflammation, NF- κ B activity, oxidative stress sources, nuclear translocation of NRF2 transcription factor, and cell death were assessed. Treatment with baicalin ameliorated ethanol-induced oxidative stress, inflammation, and cell death. Baicalin attenuated ethanol-induced proinflammatory molecules such as TNF- α, IL-1 β, MIP-2, and MCP-1 and reversed redox-sensitive transcription factor NF- κ B activation. Baicalin also modulated Kupffer cell activation in vitro. Baicalin inhibited ethanol-induced expression of reactive oxygen species (ROS) generating enzymes NOX2, p67phox, xanthine oxidase, and iNOS in addition to CYP2E1 activities. Baicalin also enhanced ethanol-induced NRF2 nuclear translocation and increased downstream target gene HO-1 as antioxidant defense. Finally, baicalin reduced significant apoptotic and necrotic cell death. Our study suggests that baicalin ameliorates chronic plus binge ethanol-induced liver injury involving molecular crosstalk of multiple pathways at the transcriptional level and through upregulation of antioxidant defense mechanism.